Could nitrogen compounds be indicators of tolerance to high doses of Cu and Fe in the cultivation of Leucaena leucocephala? - Bomfim, Nayane Cristina Pires [UNESP]; Aguilar, Jailson Vieira [UNESP]; Ferreira, Tassia Caroline [UNESP]; de Souza, Lucas Anjos; Camargos, Liliane Santos [UNESP] (Elsevier, 2023)
Nitrogen metabolism and the production of primary and secondary metabolites vary according to biotic and abiotic factors such as trace elements (TE) stress, and can, therefore, be considered biomarkers. The present study evaluated the effect of copper (Cu) and iron (Fe) TE, separately, on the metabolism of nitrogen compounds and biomass production, partitioned into shoot and roots of Leucaena leucocephala (Lam.) de Wit., and identified possible defense mechanisms linked to nitrogen metabolism. At 120 days of cultivation, the biomass production of L. leucocephala was higher when exposed to excess Fe than Cu. Nonetheless, the biomass gain (%) of plants exposed to Cu was higher, especially the biomass gains in roots. The tolerance and biomass production of L. leucocephala is related to the regulation of nitrogen metabolism and production of secondary metabolites. The biochemistry of plant metabolism against the excess of Cu and Fe TE manifested similarly, but with some specifics regarding the chemical nature of each metal. There was a reduction in the content of ureides and proteins and an increase in amino acids in the roots in relation to the increase in Cu and Fe concentrations. There was low accumulation of proline in the roots in treatments 400 and 500 mg/dm3 compared to the control for both TE. On the other hand, the total phenolic compounds in the roots increased. Our results indicate that the increased synthesis of amino acids and the accumulation of phenolic compounds is involved in the tolerance of L. leucocephala to Cu and Fe.
Keywords: Amino acids; Non-enzymatic defense mechanism; Phenolic compounds; Proline; Trace element; Ureides